Multi-Stakeholder Framework for Analyzing Electric Vehicle Adoption in Last-Mile Delivery Fleets: A Literature-Based Approach for Computational Modeling in Indonesia: A Literature-Based Approach for Computational Modeling in Indonesia - Wasesa, Haidar Aji; Prasetio, Eko Agus (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
Indonesia is experiencing an accelerated transition towards widespread electric vehicle (EV) adoption, bolstered by governmental support aimed at mitigating greenhouse gas emissions. While extensive research has been conducted on public acceptance of EVs, there remains a significant gap in the literature regarding the logistics sector, particularly in the domain of last-mile delivery. This gap is becoming increasingly salient as the e-commerce industry continues to expand, amplifying the impact of this sector. This study aims to provide a more comprehensive perspective on EV adoption by logistics firms by incorporating multiple stakeholders: the logistics firm itself, government entities, receivers, and suppliers. The research develops a multifaceted framework for EV adoption that encompasses these four stakeholder groups, with a particular emphasis on the logistics firm. This firm-centric approach is further delineated into two distinct levels: managerial and end-user (i.e., couriers). The proposed framework is designed to be implemented within computational modeling paradigms, facilitating deeper insights into how various factors surrounding logistics firm operations influence the electrification of last-mile delivery processes. This approach allows for a more nuanced understanding of the intricate relationships and interactions between stakeholders and operational variables in the context of EV adoption within the logistics sector.